Economic Uncertainty And The Demand For Money In South Africa - Tan, Wen Hsien (Universiti Malaysia Sarawak (UNIMAS), 2016)
This study examines the importance of economic uncertainty as one of the determinant of money demand function in South Africa by determining the long-run relationships between the real money demand (RMI, RM2, and RM3) and the economic uncertainty, and other control variables as well. The period of study employed is from 2000Q1 to 2014Q4. The GARCH methodology is employed at first to construct the economic uncertainty index (EUI). Then, the long-run relationships are determined by the Johansen cointegration test. The result shows there is a long-run relationship between each real money demand and the control variables. Stable real money demand function for RM 1, RM2, and RM3 models are resulted from the CUSUM and CUSUMSQ tests. However, there is only one model which all control variables are significant to the real money balance, which is RM3 model. This indicates that the RM3 is suitable to be employed as indicator for monetary policy or inflation targeting policy in South Africa to predict the trend of inflation in future and whereby some effective precautions or strategies can be recommended for encountering the shocks or uncertainty in future.